Understanding the impact of sociosexual interactions on sleep using Drosophila melanogaster as a model organism - Mishra, Sukriti; Sharma, Nisha; Lone, Shahnaz Rahman (Frontiers in Physiology, 2023)
Sleep is conserved across species, and it is believed that a fixed amount of sleep is needed for normal neurobiological functions. Sleep rebound follows sleep deprivation; however, continuous sleep deprivation for longer durations is believed to be detrimental to the animal’s well-being. Under some physiologically demanding situations, such as migration in birds, the birth of new offspring in cetaceans, and sexual interactions in pectoral sandpipers, animals are known to forgo sleep. The mechanisms by which animals forgo sleep without having any obvious negative impact on the proper functioning of their neurobiological processes are yet unknown. Therefore, a simple assay is needed to study how animals forgo sleep. The assay should be ecologically relevant so it can offer insights into the physiology of the organisms. Equally important is that the organism should be genetically amenable, which helps in understanding the cellular and molecular processes that govern such behaviors. This paper presents a simple method of sociosexual interaction to understand the process by which animals forgo sleep. In the case of Drosophila melanogaster, when males and females are in proximity, they are highly active and lose a significant amount of sleep. In addition, there is no sleep rebound afterward, and instead, males engaged in sexual interactions continue to show normal sleep. Thus, sexual drive in the fruit flies is a robust assay to understand the underlying mechanism by which animals forgo sleep.